Nanjing Library’s Reference Service Yesterday, Today and Tomorrow - Bing, Wang (Advances in Social Sciences Research Journal, 2018)
This paper systematically reviews the history of Nanjing Library reference service as well as its achievements today. It traces Nanjing Library’s development from its predecessor Jiangnan Library, National Central Library to Nanjing Library, and examines each stage from three perspectives: 1) book collection; 2) service measures and bibliography writings; and 3) consulting service cases and senior experts. It also anticipates Nanjing Library’s reference service in the next 3 to 5 years, observing four trends of development: 1) domestic and foreign cooperation, 2) service for party and government organizations, 3) service for scientific research and production, and 4) new technology and new media application.